The Influence of The 5E Learning Cycle Strategy with A Link Map on Students' Mastery of Physics Concepts and Science Process Skills - Dian Farida Rosanti; Markus Diantoro; Sentot Kusairi; Erni Yulianti (Jurnal Pendidikan Sains, 2023)
Link maps help students correlate interconcepts in order to facilitate students mastery of the concept learned. The researcher accompanied the link map in learning to find out its effect on concept mastery and students science process skills. This study used a quasi-experimental research design by providing a posttest only for the control group. The sample consisted of two classes, divided into an experimental class and a control class. The experimental class was taught using the 5E learning cycle strategy accompanied by a link map, and the control class was taught using the 5E learning cycle strategy only. The results of the analysis showed that there were differences among students who studied using the learning cycle with link maps and students who studied using the 5E learning cycle only. The further test result indicated that students who learned using the 5E learning cycle with a link map had better concept mastery of physics and science process skills than those who studied using the 5E learning cycle alone.DOI: 10.17977/jps.v11i12023p027